2019
DOI: 10.1080/2162402x.2019.1659096
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial modulation of the tumor microenvironment and generation of anti-tumor responses by TLR9 agonist lefitolimod alone and in combination with checkpoint inhibitors

Abstract: Activation of Toll-like receptor 9 (TLR9) is known to foster innate and adaptive immune responses and thus improve immune-mediated control of malignant disease. Lefitolimod is a potent TLR9 agonist without chemical modification developed for immunotherapeutic strategies. Modulation of the tumor microenvironment (TME) is a crucial requirement for the response to various immunotherapies: Immunogenic (“hot”) tumors, characterized by their T cell-infiltrated TME, respond better compared to non-immunogenic (“cold”)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…This is because there are fewer TILs in CT26 tumor tissues. 51 Thus, our study established that combined treatment could significantly inhibit the growth of tumor cells. This combined treatment strategy could be further extended to other fields including chronic infectious disease, particularly for the control of viral infection.…”
Section: Discussionmentioning
confidence: 76%
“…This is because there are fewer TILs in CT26 tumor tissues. 51 Thus, our study established that combined treatment could significantly inhibit the growth of tumor cells. This combined treatment strategy could be further extended to other fields including chronic infectious disease, particularly for the control of viral infection.…”
Section: Discussionmentioning
confidence: 76%
“…MGN1703 is a potent, clinical-stage TLR9 agonist which has recently been described [10]. The mouse anti-mouse CTLA-4 antibody 9D9 is an exceptionally efficient depleter of Tregs when expressed with the mouse IgG2a isotype, and is not subject to antibody-mediated neutralization over repeated administration as is the hamster-derived 9H10 clone used previously [11].…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, the addition of checkpoint blockade improves intratumoral ratios of CD8 T cells relative to suppressive stroma in the uninjected lesion and improves functional attributes of these critical effectors of anti-tumor immunity. Finally, we show that by combining both an enhanced potency TLR9 agonist (MGN1703 [10]) and a depletion-optimized CTLA-4 antibody (9D9-mIgG2a [11]), half of pre-implanted parental B16-F10 melanoma can be cured.…”
Section: Introductionmentioning
confidence: 99%
“…Another studies revealed that CpG-ODN can revert resistence to PD-1 blockade therapy by expending CD8+ T cells in colon cancer animal model, enhances the efficacy of anti-PD-1 in head and neck cancer animal model (198,199). CpG-ODN modulates tumor microenvironment, turns "cold" tumor into "hot" tumor, enhances the anti-tumor effect of immune checkpoint blockade in colon cancer animal model (200). Moreover, CpG-ODN delivered by inhalation is capable of priming T-cell responses against a poorly immunogenic lung tumor (201).…”
Section: Combination Therapy With Cpg-odns and Immune Checkpoint Inhimentioning
confidence: 99%